1997
DOI: 10.1007/bf02820870
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cardiac muscarinic receptor and ischemic preconditioning effects in in situ rat heart

Abstract: Activation of cardiac muscarinic receptors by vagal stimulation decreases cardiac work, which may have a protective effect against ischemic injury. To determine whether cardiac muscarinic receptors contribute to the mechanisms of preconditioning effects, we examined the effect of carbachol on ischemia/reperfusion damage and the effect of vagotomy on cardioprotection induced by ischemic preconditioning. Rats were subjected to 30 min of left coronary artery occlusion followed by 30-min reperfusion in situ. Pre-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…It may be related to stimulation of the muscarinic receptors. Several studies have demonstrated that stimulation of muscarinic receptors improves functional recovery of the heart after ischemia [23,24]. Therefore, it is conceivable that M3-mAChR could be a target for protecting the heart from ischemiainduced injury.…”
Section: Discussionmentioning
confidence: 99%
“…It may be related to stimulation of the muscarinic receptors. Several studies have demonstrated that stimulation of muscarinic receptors improves functional recovery of the heart after ischemia [23,24]. Therefore, it is conceivable that M3-mAChR could be a target for protecting the heart from ischemiainduced injury.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, ACh was shown to be as potent as adenosine in protecting the myocardium against lethal ischemia/reperfusion injury (7, 59, 64, 80). Cardioprotection induced by ACh appears to be mediated via activation of muscarinic receptors and subsequent modulation of the activity of ATP-dependent potassium channels (7, 59, 80). …”
Section: Modulation Of Myocardial Ischemia/reperfusion Injury By Neurmentioning
confidence: 99%
“…These substances increase cGMP via direct stimulation of myocardial cells or via the endothelium. It was reported that the cGMP levels in preconditioned hearts are higher than in nonpreconditioned hearts (13)(14)(15). Since cGMP can induce protein phosphorylation via protein kinase G (PKG) activation, the involvement of PKG-dependent phosphorylation in ischemic preconditioning is expected.…”
mentioning
confidence: 99%